MEDIATING ROLE OF BRAND LOVE ON THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT INNOVATION ON TOURIST REVISIT INTENTION - Ni Putu Ayu Trefi Cahaya Wati; Wayan Ardani; I Gusti Ayu Diah Werdhi Srikandi WS; Anak Agung Elik Astari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
While Bali's hospitality industry has rebounded strongly in the post-pandemic era, individual hotels face the critical challenge of declining customer loyalty amidst high occupancy. This study investigates the mechanism through which Customer Relationship Management (CRM) Innovation influences Revisit Intention, with Brand Love posited as a key mediator. A quantitative approach was employed, using a survey of 168 guests of Bintang Bali Resort, selected via purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the measurement and structural models. The results confirm that CRM Innovation has a significant positive effect on both Brand Love (β = 0.787, p < 0.001) and Revisit Intention (β = 0.440, p < 0.01). Brand Love also directly influences Revisit Intention (β = 0.377, p < 0.05). Crucially, Brand Love partially mediates the relationship between CRM Innovation and Revisit Intention (β = 0.297, p < 0.05), indicating that emotional attachment is a vital pathway through which CRM drives loyalty. This research addresses a gap in the literature by empirically testing the mediating role of Brand Love in the CRM-Revisit Intention relationship within the hospitality context. It moves beyond a direct-effects model, demonstrating that innovative CRM practices are most effective when they cultivate emotional connections, thereby offering a more nuanced understanding of customer retention dynamics. Hotel managers should transcend transactional CRM by focusing on strategies that build emotional bonds. This includes fostering a sense of shared commitment, leveraging technology for personalized experiences, and creating positive emotional experiences that encourage guests to return and promote the brand socially.